Tora! Tora! Tora! - Balsam, Martin; Cotten, Joseph; Yamamura, Soh.; Fleischer, Richard; Williams, Elmo. ([S.l.] : Foxvideo, 1994)
An epic and spectacular account of the events leading up to the Japanese attack on Pearl Harbour on Sunday, December 7, 1941- told from both the American and Japanese viewpoints and portraying in chilling detail the diplomatic blunders committed by both countries prior to the attack.
Copy available in DVD format
Martin Balsam, Joseph Cotten, Soh Yamamura.
Keywords: Pearl Harbor (Hawaii), Attack on, 1941.; World War, 1939-1945 -- Motion pictures and war; War films and programs